2021
DOI: 10.1136/oemed-2020-106973
|View full text |Cite
|
Sign up to set email alerts
|

Adverse social behaviour at the workplace and subsequent physician certified sick leave: a three-wave prospective study of the general working population in Norway

Abstract: ObjectivesWe aimed to provide an integrated picture of the relationship between different facets of adverse social behaviour (ASB) at the workplace and sick leave.MethodsData from a randomly drawn prospective cohort of the general working population. Eligible respondents were interviewed in 2009, 2013 or 2016, and were registered with an employee relationship of at least 50 working days in the national register the year following the survey interviews (n=21 674 observations/13 470 respondents). We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…On the contrary, the risk of workplace bullying is decreased when employees experienced higher levels of influence at work and quality of leadership. These findings, which strengthen the conclusions of previous studies [15], suggest that increased efforts to improve the psychosocial work environment are needed in contemporary workplaces as a crucial means for reducing the incidence of mental health outcomes-especially depression-which are established outcomes of exposure to workplace bullying [1][2][3]5,9,52]. This is imperative in light of previous studies showing the detrimental consequences of depression for employees' workability [53], companies [54], and the social security system [55].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…On the contrary, the risk of workplace bullying is decreased when employees experienced higher levels of influence at work and quality of leadership. These findings, which strengthen the conclusions of previous studies [15], suggest that increased efforts to improve the psychosocial work environment are needed in contemporary workplaces as a crucial means for reducing the incidence of mental health outcomes-especially depression-which are established outcomes of exposure to workplace bullying [1][2][3]5,9,52]. This is imperative in light of previous studies showing the detrimental consequences of depression for employees' workability [53], companies [54], and the social security system [55].…”
Section: Discussionsupporting
confidence: 75%
“…An increasing number of prospective studies has pointed to a causal link between workplace bullying (also referred to as mobbing) and reduced mental health, especially depression [1][2][3][4][5]. Workplace bullying is also associated with costs for workplaces and societies, as it increases the risk of turnover [6,7], sickness absence [8,9], and disability retirement [10,11]. The identification of possible antecedents of workplace bullying is therefore crucial to inform preventive actions aimed at countering the phenomenon and its adverse impact on mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier studies have also found evidence that there is an association between other types of adverse psychosocial work environment characteristics, such as high demands and low control and low support and justice, and stress-related health problems, such as different forms of anxiety-and depressive disorders, as well as levels of sickness absence (Duchaine et al 2020;Nieuwenhuijsen et al 2010;Slany et al 2014;Stansfeld and Candy 2006;Sterud et al 2021). Like other job stressors exposure to threatening and highly challenging actions such as violence and/or threats of violence, especially during an extended period without recuperation time, could potentially result in various forms of stress reactions such as an increase in blood pressure and heart frequency as well as higher rates of inflammation (Kivimäki and Steptoe 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies have suggested that exposure to workrelated violence and/or threats of violence is associated with an increased risk of different types of negative mental health consequences such as depression, fatigue and nervousness (Rudkjoebing et al 2020(Rudkjoebing et al , 2021. Additionally, several previous studies have suggested that there is an association between exposure to work-related violence and/or threats of violence and sickness absence (Aagestad et al 2016;Friis et al 2018;Niedhammer et al 2013;Nyberg et al 2021;Slany et al 2014;Sterud et al 2021). However, many previous studies focusing on exposure to violence and/or threats of violence and sickness absence have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…A review of prospective studies on workplace bullying and sickness absence (Nielsen et al, 2016) and three recent prospective investigations [ 20 , 21 , 22 ] indicate that workplace bullying is a risk factor for sickness absence. However, all of these studies were carried out in the Nordic countries, except one that was conducted in Belgium [ 23 ].…”
Section: Introductionmentioning
confidence: 99%